Child health, human capital and adult financial behavior - Marc-André Luik (Helmut-Schmidt-Universität - Universität der Bundeswehr Hamburg, Fächergruppe Volkswirtschaftslehre, 2016)
In this work, utilizing yearly variation between biological siblings, we test for a correlation between poor child health and adult household financial behavior, i.e. risky asset market participation. Using regression and decomposition techniques, we test if this long reach of child health operates through cognitive and non-cognitive skills. Our results indicate a negative correlation of roughly -4.1 percentage points conditional on demographics and family background. Slightly more than half of this correlation can be explained by differences in cognitive and non-cognitive skills. This work highlights the importance of good child health for adult financial behavior.
Keywords: D14; I1; J24; G11; 330; portfolio choice; human capital; child health